Athletics Australia annual report 2007-08 (Annual report Athletics Australia, 2008)
The High Performance Program objectives are to create a national junior development program, establish a network of National High Performance Centres for coaches and athletes and to be a top 10 athletics nation by 2012 (and beyond). In 2007-08 there was a strong focus on recognising, developing and accrediting coaches to ensure that Athletics Australia led the way in best practice and that we, as an organisation, could streamline coaching skills and training. This is an ongoing project and by the end of 2009 only accredited athletics coaches will be recognised by the sport. Our High Performance objective is to build a focused and transparent system for high performance that delivers exceptional performance outcomes in a cost effective manner by 2012. To achieve this high performance objective, we implemented two core strategies: o The establishment of a network of at least five event-focused National High Performance Centres (NHPCs). The aim of these NHPCs is to provide coaches and athletes access to the best support infrastructure within the State Institute of Sport/State Academy of Sport (SIS/SAS) framework. We already have some of these centres in place: ACT (400m, 400H and jumps); NSW (sprints and relays); Victoria (Distance) and WA (pole vault). 2008 also saw the appointment of Matt Horneman to the position of National Event Coordinator - Throws. o The creation of a national junior development program to identify and nurture talented young athletes. In 2008,the Elite Junior Development pathway continued with a new National Under 17 Development Squad being selected. The development of this group is guided by the National Youth Event Coaches (NYECs). Once again we have also chosen a National Under 19 Talent Squad, which will meet for two camps. Coach development opportunities are provided by the National Coaching Coordinator, Michael Poulton, for all personal coaches who attend the camps. Athletics International personally sponsors and supports the National Under 19 talent squad and provides individual mentors for each squad athlete. Thirty plus athletes attend the World Junior Championships in Bydgoszcz, Poland, in July where they will all have the opportunity to compete on the international stage against the world's best junior athletes. These strategies for our high performance have been undergoing review throughout 2008 with the intent of refining the strategies from 2009-12 and to seek further funding from the Australian Sports Commission for the next Olympiad. A key part of the future strategy will be coach development and, as a step in the direction of taking greater control of coaching as recommended in the Elliott Report, we assumed responsibility for coach accreditation from 1 April 2008. Our High Performance Program has selected a youthful team for the Beijing Olympics in August and we have high expectations they will establish a strong base of athletes around whom the 2012 London Team will be built. The "Athletics for the Outback" program is entering its fourth year and has had some very exciting results with more communities being involved in athletics as a sport of choice. Through the program many coaches are being accredited and are delivering coaching programs on a weekly basis. The introduction of the Athletics for the Outback Internet challenge gives remote schools and communities the tool to compete against others even in a different State or Territory. The Jump Start to London 2012 program has seen fantastic results with 52 Indigenous athletes achieving a national qualifying standard over our All Schools, Under 20/23 and open title meets. From the 52 qualifiers 30 medals were won. The future of this program looks very bright.